Isolation and identification of kaempferol from jangkang (Homalocladium platycladum (F. Muell) Bailey) leaves and its antibacterial activity - Maulita Cut Nuria; Wahyono .; Ratna Asmah Susidarti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Isolation and identification of kaempferol from jangkang (Homalocladium platycladum (F. Muell) Bailey) leaves and its activity against B. subtilis ATCC 9466 dan S. typhi ATCC 1408 has been done. The dried ground leaves (300.04 gram) were macerated with petroleum ether, chloroform and methanol respectively. The methanol extract was the most active extract against both bacteria. Further separations of this extract using preparative thin layer chromatography yielded flavonoid glycoside. Its aglicon was identified as kaempferol based on its spectroscopic data (MS, IR, and UV-Vis) and UV spectrum (densitometry). This compound shows iradical zone of 6.62 mm (Bacillus subtilis) and 6.27 mm (Salmonella typhi) at concentration of 200 µg/disk.Key words : kaempferol, jangkang, glycoside, aglicon